Quantification of polyphenol content, antioxidant properties and LC-MS/MS analysis in Malaysian indigenous rice cultivars (Oryza sativa L.) - Latiff, Norliza Abd; Din, Abd Rahman Jabir Mohd; Alam, Siti Atiqah Zainul; Hanapi, Siti Zulaiha; Sarmidi, Mohamad Roji (Agriculture and Natural Resources, 2019)
The study was carried out to evaluate the differences in the total phenolic content (TPC), total flavonoid content (TFC), antioxidant activities via 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic) and 2,2-diphenyl-1-picrylhydrazyl assays and quantification of targeted polyphenol compounds in Malaysian upland and wetland rice (Oryza sativa L. indica) varieties. Of note, the Bario cultivar of upland rice-seed grain extracts had the highest TPC (47.84 mg gallic acid equivalents/g), TFC (7.14 mg rutin equivalents/g) and antioxidant activities 25% higher than for the other cultivars. Ferulic acid, salicylic acid and p-coumaric acid, (the most abundant polyphenol compounds and known as a group of flavonoids responsible for high antioxidant properties) were detected in all extracts tested; upland rice of the Bario cultivar had a higher portion of ferulic acid (10.31 mg/100g), salicylic acid (3.25 mg/100g) and p-coumaric acid (1.10 mg/100g). This finding of antioxidant compounds was further confirmed using liquid chromatography combined with tandem mass spectrometry analysis in which ferulic acid produced the most substantial peak at [M-H]- m/z 193 to form the daughter ion of 134 at a retention time of 5.79 min, while p-coumaric acid was detected at m/z 163 to form the daughter ion of m/z 119 at a retention time of 4.95 min. The results indicated that the increased antioxidant quantity in upland rice could support the available upland rice grain database for the development of enriched health-promoting foods.